Understanding the spectrum of haemophagocytic lymphohistiocytosis: update on diagnostic challenges and therapeutic options. (12th June 2016) - Brisse, Ellen; Matthys, Patrick; Wouters, Carine H.
Summary: The cytokine storm syndrome 'haemophagocytic lymphohistiocytosis' (HLH) is an under‐recognized hyperinflammatory disorder, causing high morbidity and mortality risk in children and adults. It can be subdivided into a primary, genetic form and a secondary, acquired form that complicates diverse infections, malignancies and autoimmune or autoinflammatory disorders. Both subtypes present with the same spectrum of non‐specific symptoms, making accurate diagnosis and rapid treatment initiation challenging. In the last decade, increased awareness and international collaborative efforts fuelled a marked progress in diagnostic protocols and novel treatment strategies for HLH and new diagnostic guidelines are being tailored to specific secondary HLH subtypes. Therapy is gradually shifting its focus from overall immunosuppression towards targeting specific cytokines, cell types or signalling pathways underlying pathophysiology. Nevertheless, continued research efforts remain indispensable to customize therapy to individual patient needs.